Public health communication strategies: Study of their effectiveness - Faus-Real, Mireia; Alonso-Pla, Francisco; Fernández-Fernández, Cesáreo (Infonomy, 2024)
Talking about public health necessarily entails, in addition to other considerations, talking about communication. Without effective communication aimed at the population, public health will have significant impediments to its proper development and implementation, beyond other aspects of an economic, social, planning, political, etc. nature. This article focuses on discerning, from scientific evidence and analysis, the best practices and communication strategies related to public health, while identifying shortcomings and possible errors in this regard, in order to try to provide recommendations or guidelines to improve their effectiveness.
Keywords: Social communication; Public health; Communication strategies; Communication campaigns; Social networks; External communication; Social issues; Road safety; COVID-19; Artificial intelligence and Big-data; Evaluation